Antisense 2'-Deoxy, 2'-Fluoroarabino Nucleic Acid (2'F-ANA) Oligonucleotides: In Vitro Gymnotic Silencers of Gene Expression Whose Potency Is Enhanced by Fatty Acids - Naira Souleimanian; Glen F Deleavey; Harris Soifer; Sijian Wang; Katrin Tiemann; Masad J Damha; Cy A Stein (Elsevier, 2012)
Gymnosis is the process of the delivery of antisense oligodeoxynucleotides to cells, in the absence of any carriers or conjugation, that produces sequence-specific gene silencing. While gymnosis was originally demonstrated using locked nucleic acid (LNA) gapmers, 2'-deoxy-2'fluoroarabino nucleic acid (2'F-ANA) phosphorothioate gapmer oligonucleotides (oligos) when targeted to the Bcl-2 and androgen receptor (AR) mRNAs in multiple cell lines in tissue culture, are approximately as effective at silencing of Bcl-2 expression as the iso-sequential LNA congeners. In LNCaP prostate cancer cells, gymnotic silencing of the AR by a 2'F-ANA phosphorothioate gapmer oligo led to downstream silencing of cellular prostate-specific antigen (PSA) expression even in the presence of the androgenic steroid R1881 (metribolone), which stabilizes cytoplasmic levels of the AR. Furthermore, gymnotic silencing occurs in the absence of serum, and silencing by both LNA and 2'F-ANA oligos is augmented in serum-free (SF) media in some cell lines when they are treated with oleic acid and a variety of ω-6 polyunsaturated fatty acids (ω-6 PUFAs), but not by an aliphatic (palmitic) fatty acid. These results significantly expand our understanding of and ability to successfully manipulate the cellular delivery of single-stranded oligos in vitro.